Improvement of the Derjaguin-Broekhoff-de Boer Theory for the Capillary Condensation/Evaporation of Nitrogen in Spherical Cavities and Its Application for the Pore Size Analysis of Silicas with Ordered Cagelike Mesopores - Kowalczyk, Poitr; Jaroniec, M.; Kaneko, K.; Terzyk, A.; Gauden, P. (American Chemical Society, 2005)
In a previous work, we proposed an improvement of the Derjaguin-Broekhoff-de Boer (DBdB) theory for capillary condensation/evaporation in open-ended cylindrical mesopores. In this paper, we report a further extension of this approach to the capillary condensation/evaporation of nitrogen in siliceous spherical cavities. The main idea of this improvement is to employ the Gibbs-Tolman-Koenig-Buff equation to predict the variation of the surface tension in spherical mesopores. In addition, the statistical film thickness (the so-called t-curve), which is evaluated accurately on the basis of adsorption isotherms measured for MCM-41 materials, is used instead of the originally proposed t-curve to take into account the excess chemical potential due to the surface forces. It is shown that the aforementioned modifications of the original DBdB theory that was refined by Ravikovitch and Neimark have significant implications for the pore size analysis of cagelike mesoporous silicas. To verify the proposed improvement of the DBdB pore size analysis (IDBdB), two series of FDU-1 samples, which are well-defined cagelike mesoporous materials (composed of siliceous spherical cavities interconnected by short necks), were used for the evaluation of the pore size distributions (PSDs). The correlation between the spinodal condensation point in the spherical pores predicted by the nonlocal density functional theory (NDFT) developed by Ravikovitch and Neimark and that predicted by the IDBdB theory is very good in the whole range of mesopores. This feature is mirrored to the realistic PSD characterized by the bimodal structure of pores computed from the IDBdB theory. As in the case of open-ended cylindrical pores, the improvement of the classical DBdB theory preserves its simplicity and simultaneously ensures a significant improvement of the pore size analysis, which is confirmed by the independent estimation of the average pore size by the NDFT and the powder X-ray diffraction method.